COMPARISON OF EFFECTIVENESS OF CLUSTER MAPPING, FLOW CHARTING, AND DOUBLE/ TRIPLE ENTRY ON TEACHING WRITING SKILL - Sofeny, Daniar (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2019)
The study was aimed to examine the effectiveness of three writing techniques, namely Cluster Mapping, Flow Charting, and Double/ Triple Entry in improving the students’ writing skill. The research technique used was descriptive comparative technique using a quantitative approach. It compared the equations and differences as phenomena to find what factors/ situations that can cause the occurrence of a particular event. The data collection techniques were Documentation study by taking the students’ writing product and interview by giving the question and answer while face to face between the interviewer with the respondent using a tool called interview guide. The try out was conducted to measure validity and reliability. The two ways ANOVA was conducted to test the hypotheses, two –way analysis of variance with F-test at the 5% (0.05) level of significance. The subject of this study was the fourth semester English students with a total of 22 people. The English students’ writing skill using three techniques was tobe the object under the study. The findings of the study were the average writing score of students using Cluster Mapping was 56.5, the average score of students’ writing using Flow Charting was 49.6, and the average score of students’ writing using Double/ Triple Entry was 63.0. It can be concluded that those three techniques of writing skill are effective to use but the most effective is the Double/ Triple Entry technique. Keywords: cluster mapping, flow charting, double/triple entry, writing skill Keywords: Cluster Mapping, Flow Charting, Double/ Triple Entry, Writing Skill